PENGELOLAAN SURAT DINAS DAN ARSIP BAGI KEPALA SEKOLAH DAN TENAGA ADMINISTRASI SEKOLAH DASAR DI KECAMATAN JATINEGARA KOTA ADMINISTRASI JAKARTA TIMUR - Karnati, Neti; Rosyidi, Unifah; Ambar Arum, Wahyu Sri (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
Elementary school administration is an activity to support the success of the quality of education in elementary schools. The scope of school administration activities includes the management of official letters and school archives. Management of official letters and archives in primary schools is carried out by the principal, assisted by a school operator. Their ability to manage official documents and school archives is still lacking. Efforts to increase the capacity of school principals and elementary school administrative personnel can be provided with training on managing official letters and school archives. The object (target audience) of the training activities is 150 people consisting of 2 elementary school supervisors, 58 school principals, 83 school administration staff and 7 SDN teachers in Jatinegara sub-district. The partners involved are the Regional Education Office of East Jakarta Administrative City. The training has been carried out for a day on Thursday, October 8, 2020 through virtual zoom cloud metting. The training material consists of: school leadership and administration, management of official letters and management of school records. The three materials were delivered by 3 lecturers of the UNJ FIP Education Management study program with the lecture, question and answer and assignment method. The results of the training were very satisfying to the participants and the organizing committee, because all the materials had been delivered well and were very useful for all training participants.